2020
DOI: 10.1155/2020/3670412
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells from Human Exfoliated Deciduous Teeth and the Orbicularis Oris Muscle: How Do They Behave When Exposed to a Proinflammatory Stimulus?

Abstract: Mesenchymal stem cells (MSCs) have been studied as a promising type of stem cell for use in cell therapies because of their ability to regulate the immune response. Although they are classically isolated from the bone marrow, many studies have sought to isolate MSCs from noninvasive sources. The objective of this study was to evaluate how MSCs isolated from the dental pulp of human exfoliated deciduous teeth (SHED) and fragments of the orbicularis oris muscle (OOMDSCs) behave when treated with an inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…MHC class II antigen HLA-DR binds to T-cell receptors during the immune response (Yang et al, 2021). SHED do not express HLA-DR even after stimulation with IFN-γ (Junior et al, 2020). With the properties of immunomodulatory functions, SHED is considered one of the most attractive cell sources for regenerative medicine (Sui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MHC class II antigen HLA-DR binds to T-cell receptors during the immune response (Yang et al, 2021). SHED do not express HLA-DR even after stimulation with IFN-γ (Junior et al, 2020). With the properties of immunomodulatory functions, SHED is considered one of the most attractive cell sources for regenerative medicine (Sui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SHED have a stronger proliferative capacity than BMMSs (Kunimatsu et al, 2018). Meanwhile, SHED have outstanding immunomodulatory and immunosuppressive potential (Junior et al, 2020), thus becoming promising candidates for transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Another crucial cytokine, HLA‐G, is a nonclassical MHC class I involved in immunomodulation by inhibiting the activation of natural killer cells and effector T cells [ 48 , 49 ]. A previous study reported that simulating the inflammatory environment of dental MSCs by incubating the cells with the pro‐inflammatory cytokine interferon‐γ results in increased HLA‐G expression in an interferon‐γ‐dependent manner [ 50 ]. Co‐culture experiments with peripheral blood mononuclear cells also drive the increased expression of IDO, soluble HLA‐G and HGF in MSCs [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…, prostaglandin-endoperoxide synthase 2, prostaglandin I2 synthase, FAM20A (FAM20A golgi-associated secretory pathway pseudokinase), FAM20C (FAM20C golgi-associated secretory pathway kinase) and glycoprotein A repetitions predominant (GARP)/leucine rich repeat containing 32] that were upregulated. Moreover, MSCs isolated from the dental pulp of human exfoliated deciduous teeth and fragments of the orbicularis oris muscle showed enhanced immunomodulatory properties probably linked to increased HLA-G expression[ 48 ] in the presence of IFN-γ. Indeed, a recent study highlighted the key role of the HLA-G gene in modulating the immune response, and the importance of its polymorphisms and alleles associated with the outcome of the transplants[ 49 ].…”
Section: Preconditioning Strategies Of Mscsmentioning
confidence: 99%